2018
DOI: 10.1002/2017gl076521
|View full text |Cite
|
Sign up to set email alerts
|

Global Changes in Drought Conditions Under Different Levels of Warming

Abstract: Higher evaporative demands and more frequent and persistent dry spells associated with rising temperatures suggest that drought conditions could worsen in many regions of the world. In this study, we assess how drought conditions may develop across the globe for 1.5, 2, and 3°C warming compared to preindustrial temperatures. Results show that two thirds of global population will experience a progressive increase in drought conditions with warming. For drying areas, drought durations are projected to rise at ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
298
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 572 publications
(352 citation statements)
references
References 92 publications
8
298
0
5
Order By: Relevance
“…Thus, we further suggest these differential trends in dryness for NorCal and SoCal may be caused by the PDO/ENSO-related seesaw of hydroclimatic variability over the Pacific Northwest and Southwest. The climatic drying might be partly attributed to the anthropogenic warming-induced increase of atmospheric evaporative demand (MacDonald et al, 2016;Naumann et al, 2018;Williams et al, 2015). It is consistent with Deitch et al (2017) who reported significantly reduced (increased) precipitation during the past half-century in SoCal (NorCal).…”
Section: Drought and Climate Change In Californiasupporting
confidence: 80%
“…Thus, we further suggest these differential trends in dryness for NorCal and SoCal may be caused by the PDO/ENSO-related seesaw of hydroclimatic variability over the Pacific Northwest and Southwest. The climatic drying might be partly attributed to the anthropogenic warming-induced increase of atmospheric evaporative demand (MacDonald et al, 2016;Naumann et al, 2018;Williams et al, 2015). It is consistent with Deitch et al (2017) who reported significantly reduced (increased) precipitation during the past half-century in SoCal (NorCal).…”
Section: Drought and Climate Change In Californiasupporting
confidence: 80%
“…We employed a multimodel ensemble of different monthly climatic and hydrological variables derived from the CMIP5 global climate models (GCMs) under four different representative concentration pathway (RCP) concentration scenarios (2.6, 4.5, 6.0 and 8.5) for the period 2005–2100 (Taylor et al ., ). Assessing drought conditions based on multimodel means is a common procedure in future drought studies (Dai et al ., ; Naumann et al ., ). The following variables were used: (a) precipitation; (b) maximum and minimum air temperatures; (c) relative humidity; (d) incoming short‐wave solar radiation; (e) total column soil moisture; and (f) surface runoff.…”
Section: Methodsmentioning
confidence: 99%
“…This data set has been used in earlier publications to estimate future changes of heat waves (Dosio et al, ) and drought (Naumann et al, ). We also validate the climate simulation for the specific purposes of this study by comparing the HMD and the SPEI mean values and the values characterized by a return period of 10 years computed on the simulation ensemble with respect to the same values computed from the observations (see Figure S4 and Text S4).…”
Section: Datamentioning
confidence: 99%